PELATIHAN PEMBUATAN PUPUK ORGANIK PADA KELOMPOK TANI DAN TERNAK DI DESA LAYANSARI KECAMATAN GANDRUNGMANGU - Bayu Sudrajat; Syafiqul Majid; Fatma Nur Fadila; Pifki Farika Azzahra (Rumah Jurnal INSIMA Cilacap, 2025)
Training in making organic fertilizer is an effective strategy to improve environmental quality and community potential, especially in Indonesia where the majority of the population is involved in the agricultural sector. This training aims to reduce dependence on inorganic fertilizers which have a negative impact on the environment, by utilizing agricultural waste and animal waste as raw materials for organic fertilizer. Through training, the community not only acquires technical skills in making fertilizer, but also increases awareness of the importance of waste management and environmental conservation. Apart from that, the use of organic fertilizer can also reduce agricultural production costs and provide additional economic opportunities for farmers. Thus, this training plays an important role in maintaining soil quality, increasing land productivity, and supporting agricultural sustainability. The service methods used in this activity are planning, observation, training and discussion. This activity is carried out with direct practice and discussion. The result of this community service is training in Layansari Village equipping the community with fermentation techniques to process goat kohe into organic fertilizer, increasing soil fertility, and reducing the use of chemical fertilizers for more sustainable agriculture.